Single-Cell RNA Sequencing Reveals the Heterogeneity of Tumor-Associated Macrophage in Non-Small Cell Lung Cancer and Differences Between Sexes - Yang, Qi; Zhang, Hongman; Wei, Ting; Lin, Anqi; Sun, Yueqin; Luo, Peng; Zhang, Jian (Frontiers in Immunology, 2021)
Non-Small Cell Lung Cancer (NSCLC) is a disease with high morbidity and mortality, which has sex-related differences in prognosis and immunotherapy efficacy. However, the difference in the mechanisms remains unclear. Macrophages, characterized by high plasticity and heterogeneity, act as one of the key cells that exert anti-tumor effects in the tumor microenvironment (TME) and play a complicated role in the process of tumor progression. To elucidate the subtype composition and functional heterogeneity of tumor-associated macrophages (TAMs) in NSCLC and further compare the sex-mediated differences, we conducted a single-cell level analysis in early-stage smoking NSCLC patients, combined with ssGSEA analysis, pseudotime ordering, and SCENIC analysis. We found two universally presented immune-suppressive TAMs with different functional and metabolic characteristics in the TME of NSCLC. Specifically, CCL18+ macrophages exerted immune-suppressive effects by inhibiting the production of inflammatory factors and manifested high levels of fatty acid oxidative phosphorylation metabolism. Conversely, the main metabolism pathway for SPP1+ macrophage was glycolysis which contributed to tumor metastasis by promoting angiogenesis and matrix remodeling. In terms of the differentially expressed genes, the complement gene C1QC and the matrix remodeling relevant genes FN1 and SPP1 were differentially expressed in the TAMs between sexes, of which the male upregulated SPP1 showed the potential as an ideal target for adjuvant immunotherapy and improving the efficacy of immunotherapy. According to the early-stage TCGA-NSCLC cohort, high expression of the above three genes in immune cells were associated with poor prognosis and acted as independent prognostic factors. Moreover, through verification at the transcription factor, transcriptome, and protein levels, we found that TAMs from women showed stronger immunogenicity with higher interferon-producing and antigen-presenting ability, while men-derived TAMs upregulated the PPARs and matrix remodeling related pathways, thus were more inclined to be immunosuppressive. Deconstruction of the TAMs at the single-cell level deepens our understanding of the mechanism for tumor occurrence and progress, which could be helpful to achieve the precise sex-specific tumor treatment sooner.